Genetic structure and demographic history of two west african colobine monkeys: the effects of habitat fragmentation and hunting - Oliveira, Rúben Filipe Sousa de (2017)
Tese de mestrado, Biologia da Conservação, Universidade de Lisboa, Faculdade de Ciências, 2017